GOVERNMENT INTERVENTION ON SPREAD - Nevi Danila (Akutansi Bisnis & Manajemen ( ABM ), 2000)
We find that during 1985 to 1987 intervention in the Japanese yen widened the spread and intervention in the Deutsche mark did not have any influence on spread. This finding is supported by several authors: Federal Reserve intervention either increased the volatility of yen/US dollar or had no impact on the volatility of DM/US$ during the period 1985-1991.